Factors associated with prolonged viral shedding in COVID-19 infection: A retrospective cohort from Karachi, Pakistan - Lokesh Kumar; Ishfaque Ahmed; Chanchal Kumari; Nosheen Nasir (PLoS ONE, 2025)
Background The implications of prolonged viral shedding in COVID-19 are of major public health concern. There are several studies elucidating the impact on transmission; there is a lack of data on outcomes. The objective of this study was to identify factors associated with prolonged viral shedding and its impact on disease outcomes in COVID-19. Methods This retrospective cohort was conducted on hospitalized throat swab-PCR confirmed COVID-19 patients admitted between March 01, 2020, and June 07, 2020, at the Aga Khan University Hospital in Karachi, Pakistan. Demographic, treatment and successive SARS CoV-2 PCR data were extracted from medical records using a structured proforma. Prolonged viral shedding was defined as PCR positivity greater than or equal to 15 days from the first positive PCR. Outcomes studied included in-hospital mortality, length of stay, and requirement of mechanical ventilation. Results Out of 435 patients, only 110 could be assessed for time to negativity. 47 patients (42.7%) had viral shedding for more than 15 days compared to 63 (57.3%) patients with viral shedding for less than 15 days. The median duration of time to negativity in the prolonged shedding group was 25 days compared to 9 days in the other group. The median age was 54, and it was similar in both groups. Most of the patients had mild diseases in both groups. There was no statistically significant difference between either of the groups in terms of in-hospital mortality (2/47 versus 1/63) and length of stay (9 versus 8) days. Conclusion This study did not find any factors associated with prolonged viral shedding in COVID-19, and there was no impact of prolonged viral shedding on in-hospital mortality.